О некоторых параллелях в польской и русской поэзии Х1Х-ХХ вв. (поэма Густава Зелинского Киргиз и русский перевод Георгия Гребенщикова) - Abdullina, Lucija (Acta Polono-Ruthenica, 2014)
In this article on a material of the poem Kyrgyz of the Polish poet of the XIX century G. Zelinsky and its Russian translation by the Kazakhstan writer-ethnographer of the XX century G. Grebenshchikov the creative nature of the ethnographic interest is researched. The idea of freedom embodied in the image of young Kyrgyz inspired both artists. The romantic color and lyrical identity of the texts find realistic dimensions due to lthe ethnographic realities of a steppe landscape.